Placebo-controlled pilot study of the effects of an eggshell membrane-based supplement on mobility and serum biomarkers in dogs with osteoarthritis. (November 2019) - Muller, C.; Enomoto, M.; Buono, A.; Steiner, J.M.; Lascelles, B.D.X.
Highlights: This masked, placebo-controlled pilot study investigated an eggshell membrane-based oral supplement in dogs. The supplement was well tolerated over the 12-week trial period by dogs with osteoarthritis-associated pain. Compared to a placebo, the supplement was associated with a small reduction in serum inflammatory cytokine IL-2. There were variable responses in owner questionnaires measuring pain and function. Results of this pilot study support further evaluation of this supplement. Abstract: Osteoarthritis (OA) is a debilitating disease in dogs. Non-steroidal anti-inflammatory drugs (NSAIDs) are commonly used to treat OA; however, many dogs do not obtain adequate pain relief with an NSAID alone. This pilot study evaluated the systemic anti-inflammatory and mobility enhancing effects of an eggshell membrane-based nutritional supplement in dogs with OA-associated pain and mobility impairment. Twenty-seven dogs with OA-associated pain were enrolled into a randomized, double-masked, placebo-controlled, proof of principle pilot study and received either placebo or an eggshell membrane-based nutritional supplement over a 12-week period. Inflammatory biomarkers (IL-2, IL-6, IL-8, tumor necrosis factor-α, C-reactive protein, S100A12, and N-methylhistamine) were measured at Day 0 and Day 84. Owner questionnaires (CBPI and LOAD) were completed at Day 0, Day 42, and Day 84. Differences between groups over time were calculated. Twenty-two dogs completed the pilot study. Inflammatory biomarker IL-2 decreased in the supplement group, compared to the placebo group. Although small, the difference was statistically significant at an alpha of 0.1 ( P  = 0.069). LOAD scores were numerically lower in the supplement group, but not significantly different from the placebo group at Day 0. Day 84 LOAD scores were significantly lower in the supplement group compared to the placebo group ( P  = 0.034). CBPI results did not show the same pattern. The changes in biomarkers and LOAD scores were small, and do not provide definitive evidence of positive effects. However, these pilot results provide a rationale for performing a larger placebo-controlled study of the potential effects of the eggshell membrane-based nutritional supplement.